A implantação de normas sanitárias e a disputa entre diferentes convenções de qualidade no mercado de leite na microrregião de Imperatriz-Ma - LIMA NETO, Evaristo José de (2017)
This theory has as objective to study the milk-producing region’s transformations in the micro-region of Imperatriz-MA, generated by the implementation of the Normative Instructions 51 and 62, of the Ministry of the Agriculture and Provisioning - MAPA, trying to verify how cattle farmers, family farmers, informal cheese dairies and dairy products are positioned at that market, working their own criteria on what they consider as the quality of the milk and the cheese that is produced. Edited respectively in the years of 2002 and 2011, these normative instructions constituted in the main devices of sanitary regulation for the section, establishing technical criteria for the production, identity, quality, collects and transport of the milk. In Imperatriz's micro-region, the largest milk-producing region of Maranhão, the effects of those Normative Instructions were felt indeed starting from the year of 2012, when the State’s Public Ministry-MPE began a interinstitutional campaign to combat to the "clandestine" milk and cheese, produced in establishments without formal registration in the organs of sanitary inspection. As a consequence of this campaign a rearrangement of the market of regional milk was observed, with the modification of the commercial relationships between the primary producers of milk and the formal (industries of dairy products) and informal (cheesemakers) units of improvement, when the dairy products assumed a position of defenders' to the implantation of the Normative Instructions, while the other actors seek to loosen up the application of those. Located in the field of the Economical Sociology, this study tried to approach the problem in subject being guided by the ideas that the processes of establishment of quality criteria constitute a preliminary moment to the establishment of the mercantile exchange and, that the quality of a product is not defined starting from an universal reference, but starting from values socially shared ruled in different notions of "justice" and “common good." Starting from the model of cités, elaborated by Boltanski and Thevénot (1991) it was possible to identify in the area studied two production models and improvement of milk in dispute, corresponding conceptually to the models of the conventions of the domestic world and of the industrial world, represented, respectively, by producers identified as artisanal cheesemakers and by the industry of dairy products. In this sense, these two worlds were described and analysed being looked for to apprehend the principles and evaluation criteria, mobilized by the actors involved in situations characterized by disputes around the quality patterns. In a more specific way, the milk, the actante (CALLON 2006) more present in the studied chain, was followed in its path to be transformed in cheese, when taken by the hands of the industry of dairy products, or by the hands of the artisanal cheesemakers, revealing in these courses the attributes of the human and non-human actantes involved in the improvement processes, the justifications and the ideological debates that emerge in these contexts, the differences in the verification forms and control inherent to each one of them, and the elements the factors that will compose the cognitive pictures in each world. These procedures allowed, finally, to summarize the main impacts and consequences of the dispute process for the quality and the establishment of a new configuration to the market of milk in Imperatriz’s MRH.